(untitled) (Research, Society and Development, 2022)
Objective: to map in the literature the instruments for assessing the psychomotor development of children in Brazil. Method: this is a research protocol, based on the Joanna Briggs Institute manual, using the Prefered Reporing Items for Systematic Reviews extension for Scoping Review checklist, registered in Open Science Framework no. osf.io/vr4z3. A search and data collection will be carried out with Descriptors in Health Science and Medical Subject Headings. Studies that answer the research question will be considered eligible. Selection will take place independently by two reviewers, using Rayyan software. Disagreements will be appreciated by a third reviewer. The results will be presented through a summary table, flowchart and narrative discussion. Expected results: the present study aims to list the instruments and assessment scales of psychomotor development validated for the Brazilian population.